Responsible urban innovation with local government artificial intelligence (AI): A conceptual framework and research agenda - Tan Yigitcanlar; Juan Manuel Corchado; Rashid Mehmood; Rita Yi Man Li; Karen Mossberger; Kevin C. Desouza (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The urbanization problems we face may be alleviated using innovative digital technology.However, employing these technologies entails the risk of creating new urban problems and/orintensifying the old ones instead of alleviating them. Hence, in a world with immense technologicalopportunities and at the same time enormous urbanization challenges, it is critical to adopt theprinciples of responsible urban innovation. These principles assure the delivery of the desired urbanoutcomes and futures. We contribute to the existing responsible urban innovation discourse byfocusing on local government artificial intelligence (AI) systems, providing a literature and practiceoverview, and a conceptual framework. In this perspective paper, we advocate for the need forbalancing the costs, benefits, risks and impacts of developing, adopting, deploying and managinglocal government AI systems in order to achieve responsible urban innovation. The statements madein this perspective paper are based on a thorough review of the literature, research, developments,trends and applications carefully selected and analyzed by an expert team of investigators. Thisstudy provides new insights, develops a conceptual framework and identifies prospective researchquestions by placing local government AI systems under the microscope through the lens of re-sponsible urban innovation. The presented overview and framework, along with the identifiedissues and research agenda, offer scholars prospective lines of research and development; wherethe outcomes of these future studies will help urban policymakers, managers and planners to betterunderstand the crucial role played by local government AI systems in ensuring the achievement ofresponsible outcomes.
Keywords: 650; AI revolution; artificial intelligence (AI); community engagement; local government AI; responsible AI; responsible innovation; responsible urban innovation; smart city; urban policy; urban technology